(untitled) - Starr, Cecile (Belmont, CA, 2006)
Want an easy-to-understand non-majors biology textbook that will help you succeed in the course? A highly illustrated biology book that gives you the basics you need to understand many of the most pressing problems we face in the 21st century? Starr's issues-oriented BASIC CONCEPTS IN BIOLOGY helps you build a foundational understanding and shows you why it matters. You'll read essays on hot issues, research further, vote your position in an online poll, and then compare your votes to those of your classmates
Keywords: Biology,Physiology